2001
DOI: 10.1038/emm.2001.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal ions on the stability of metallothionein in the degradation by cellular fractions in vitro

Abstract: Metallothioneins (MT), small molecular weight metal binding proteins are known to play an important protective role against heavy metal toxicity, either as antioxidants or pre-oxidants. However, the mode of metabolic fate of MTs in various metal complexes is not clearly understood. This study was carried out to better understand the mode of selective turnover rate of various form of MT in complexes with different metals. The degradation of in vitro translated mouse 35 S-cysteine-MT was examined in lysosomal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The idea is also in agreement with results by Mello-Filho et al [46], who postulated that iron chelation by MTs might eliminate Fenton-mediated radical damage, and with the results of other groups, who showed proteolytic degradation of MTs by lysosomal cathepsins, but not by cytosolic proteolytic enzymes, suggesting that lysosomes are chiefly responsible for the turnover of MTs. It was also shown that apo-MT is quickly degraded by lysosomal proteases, while metal-conjugated MTs are surprisingly resistant, suggesting that autophagocytosed MT may remain intact for some time after binding iron [26,27]. Thus it seems justified to suggest that autophagocytosed MTs should decrease intralysosomal Fenton-type reactions, giving exactly the effects on lysosomal stability that we have found.…”
Section: Figure 8 Lysosomal Stability Following Exposure To Dfo or A supporting
confidence: 60%
See 1 more Smart Citation
“…The idea is also in agreement with results by Mello-Filho et al [46], who postulated that iron chelation by MTs might eliminate Fenton-mediated radical damage, and with the results of other groups, who showed proteolytic degradation of MTs by lysosomal cathepsins, but not by cytosolic proteolytic enzymes, suggesting that lysosomes are chiefly responsible for the turnover of MTs. It was also shown that apo-MT is quickly degraded by lysosomal proteases, while metal-conjugated MTs are surprisingly resistant, suggesting that autophagocytosed MT may remain intact for some time after binding iron [26,27]. Thus it seems justified to suggest that autophagocytosed MTs should decrease intralysosomal Fenton-type reactions, giving exactly the effects on lysosomal stability that we have found.…”
Section: Figure 8 Lysosomal Stability Following Exposure To Dfo or A supporting
confidence: 60%
“…Thus MTs have been found to protect against apoptosis/necrosis induced by oxidative stress, etoposide, cisplatin, doxorubicin and X-irradiation [23][24][25]. Apo-MTs are effectively degraded by lysosomal cathepsins, while metal-conjugated MTs are more stable [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…3,8 Indeed, yeast mutants defective in the biogenesis of the vacuole exhibit sensitivity to high levels of exogenous Cu. [39][40][41] Since metallothioneins do not transport Cu across the membrane, metallothionein-bound Cu is likely to be sequestered in the cytosol by autophagy and then supplied to the lysosome through autophagosome/lysosome fusion. Metal supply may occur through endocytosis and further lysosomal degradation of Cu-binding proteins or through transport across the lysosomal membrane, although transporters that can pump Cu inside the acidic organelles in plants and yeast remain to be identified.…”
Section: Cu Storage In the Lysosomesmentioning
confidence: 99%
“…Contrarily, attenuation of FT or HSP70 expression seems to sensitize cells to oxidative stress [192,200]. In addition, many studies have implied that autophagy with subsequent decomposition in the lysosomal compartment is the normal way for turnover of these stress proteins [78,82,88,89,141,[201][202][203].…”
Section: Discussionmentioning
confidence: 99%